THE EFFECT OF PROMOTION, SERVICE QUALITY, PRICE AND LIFESTYLE ON FIRSTMEDIA CONSUMER SATISFACTION IN THE WEST JAKARTA AREA - Dharaura Aziyasyah,; Rojuaniah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The purpose of this study was to determine how much influence promotion, service quality, price and lifestyle have on consumer satisfaction. The object of this research is Firstmedia. This study collects data with a questionnaire, the scale used for the questionnaire is the Likert scale. There are 40 statements in the research questionnaire, so the minimum number of samples required is 200 respondents. Samples were selected using purposive sampling method. The measuring instrument used to measure the questionnaire used validity and reliability tests, validity tests were carried out by sampling the product moment correlation and reliability tests using Cronbach alpha. Meanwhile, to see the relationship between variables and the effect of each independent variable on the dependent variable using the t test and the analytical tool used is Multiple Linear Regression. The results of this study are that promotion, service quality, price and lifestyle have a positive and significant effect on consumer satisfaction